Can music make you sick? : measuring the price of musical ambition - Gross, Sally-Anne; Musgrave, George, 1986- (University of Westminster Press, 2020)
It is often assumed that creative people are prone to psychological instability, and that this explains apparent associations between cultural production and mental health problems. In their detailed study of recording and performing artists in the British music industry, Sally Anne Gross and George Musgrave turn this view on its head. By listening to how musicians understand and experience their working lives, this book proposes that whilst making music is therapeutic, making a career from music can be traumatic. The authors show how careers based on an all-consuming passion have become more insecure and devalued. Artistic merit and intimate, often painful, self-disclosures are the subject of unremitting scrutiny and data metrics. Personal relationships and social support networks are increasingly bound up with calculative transactions. Drawing on original empirical research and a wide-ranging survey of scholarship from across the social sciences, their findings will be provocative for future research on mental health, wellbeing and working conditions in the music industries and across the creative economy. Going beyond self-help strategies, they challenge the industry to make transformative structural change. Until then, the book provides an invaluable guide for anyone currently making their career in music, as well as those tasked with training and educating the next generation.